Le Pont de Pierre de Charlieu (Loire). Archéologie d’un ouvrage d’art : construction et évolution architecturale - Marc Guyon (Revue Archéologique du Centre de la France)
In 2011, a preventive archeology operations, following a prescription issued by the State (DRAC Rhône-Alpes), has increased our knowledge of this bridge, seizing the opportunity to repair the item by the conseil général de la Loire.This stone bridge, which can cross the “le Sornin” River, is located south of the town of Charlieu.No summary does not indicate passages which existed in the town of Charlieu.Knowledge of the bridge through the texts is rather thin. We do not know the date of construction. Only a terrier already evokes his presence in 1432. Text mentions that it is being repaired in 1733. In 1861, her apron was extended upstream. In 1938, the three southern piers are strengthened.At present, where often the remains of bridges are destroyed by excavators and nobody can intervene, the archaeological investigation has to make substantial data on the knowledge of this bridge.According to construction contracts, this type of foundation is well known from the fifteenth century, but it remains poorly documented archaeologically.This unique study shed light on the organization of a general raft and a foundation of piles dating back to the fifteenth century.